Environmental Management System (EMS): Trends and Research Patterns from a Bibliometric Perspective - Nurhaliza, Ajeng (Social Impact Journal, 2025)
This study aims to explore the development trends and research collaboration patterns in the field of Environmental Management Systems (EMS) using a bibliometric analysis approach. EMS plays a crucial role in supporting sustainable environmental governance and has gained increasing attention in the global academic community over the past decade. The study uses quantitative methods through bibliometric analysis with data obtained from the Dimensions database, focusing on publications from 2021 to mid-2025. A total of 236 relevant publications were analyzed using VOSviewer software to map publication trends, country and institutional collaboration networks, co-authorship patterns, and keyword co-occurrences. The results reveal a significant increase in EMS-related research publications starting from 2021, peaking in 2024. Indonesia emerged as a central actor in EMS research networks, both in terms of publication volume and collaboration strength. Institutions such as the Bandung Institute of Technology and Padjadjaran University were identified as major contributors. Furthermore, the analysis of co-occurring keywords indicates a shift in research focus from structural and technical aspects of EMS towards issues related to policy, implementation challenges, and the role of technology. This study concludes that EMS has evolved into a dynamic and multidisciplinary research area with growing global interest. The strengthening of collaborative networks among researchers, institutions, and countries is pivotal in enhancing the quality and impact of EMS-related research. These findings offer strategic insights for academics, practitioners, and policymakers to optimize research networks and support more effective and sustainable EMS implementations.